How to choose the proper words? The process of vocabulary standardization in Putonghua - Kurpaska, Maria (Lingua Posnaniensis, 2020)
As with most fields of life, China can trace its history of word standardization back to ancient times, when the first dictionaries (such as Erya, ca. 3rd century B.C.) appeared. Modern Standard Chinese used in Mainland China – Putonghua – has been subject to standardization since its proclamation as the official national language of China in 1956. The definition states quite clearly that its base is formed by the Northern dialects. This statement concerns also vocabulary. However, it is not a simple matter to make a choice of words which are to be used throughout the country. On the one hand, the so-called “Northern dialects” are spoken by almost 70% of the Han Chinese population, i.e. by about 800 million people. Although the Northern dialects are said to be quite uniform, the vast area that they cover must bring diversity in vocabulary. On the other hand, the remaining 30% of the Han Chinese speak a range of mutually unintelligible tongues, which are bound to penetrate the Northern dialects. The aim of this paper is to show how the lexicon of Putonghua is being codified. An attempt will be made to reveal how the basic vocabulary was selected during the forming of Putonghua in the 1950s. Some of the tools used by the State Language Commission in order to control the process of vocabulary standardization will be described. Moreover, the paper intends to describe the ongoing changes in the Chinese lexicon. It will show the sources of new words that are gradually accepted into the authoritative dictionaries of modern Chinese.